Frontonia lynni n. sp., a new marine ciliate (Protozoa, Ciliophora, Hymenostomatida) from Qingdao, China - Long, Hongan; Song, Weibo; Gong, Jun; Hu, Xiaozhong; Ma, Honggang; Zhu, Mingzhuang; Wang, Mei (Zootaxa, 2005)
The morphology, infraciliature and silverline system of a new marine ciliate, Frontonia lynni n. sp., isolated from a sandy beach at Qingdao, China, was investigated using live observation and silver staining methods. The new species is recognized by the combination of the following characters: body about 100–210 x 70–150 µm in vivo, elliptical in outline; dorsoventrally flattened (3:1); one large contractile vacuole equatorially located, right of median; 71–83 somatic kineties and three vestibular kineties; small oral cavity with peniculi 1 and 2 each having four ciliary rows and peniculus 3 possesses five gradually shortened rows.